Impact of mixing layer height on air quality in winter - Murthy, B.S.; Latha, R.; Tiwari, Arpit; Rathod, Aditi; Singh, Siddhartha; Beig, G. (Journal of atmospheric and solar-terrestrial physics, 2020)
Air quality in Delhi is largely dependent on concentration of aerosol particulate matter with aerodynamic diameter less than 2.5 μm (PM2.5). Diurnal variation of PM2.5 is mainly determined by rates of emission, deposition, chemical reactions and turbulent mixing caused by vertical wind shear and buoyancy. Continuous observations of PM2.5, NOx and O3 along with mixing layer height (MLH) by ceilometer (Vaisala CL51) in Delhi (Lodi road) during December 2017, January and February 2018 are analyzed. Comparison of MLH in winter (December) obtained from ceilometer and radiosonde showed good agreement in 66% of the cases for stable conditions and 36% of the cases for convective conditions. Diurnal variation revealed relatively low PM2.5 and NOx during convective period coinciding with high MLH while O3 registered higher concentration proportional to solar radiation. PM2.5 mass density was found to be inversely correlated to MLH during convective period. The mass density decreased by 14, 13 and 7 μgm−3 in December, January and February respectively for every 100 m increase of MLH. Variation of PM2.5 normalized by MLH qualitatively illustrated the influence of MLH on air quality in terms of dilution and accumulation during convective and statically stable conditions respectively. NOx and O3 had better correlations with MLH as compared to that of PM2.5. Air quality index in Delhi during winter with very low wind speed is mainly determined by MLH except during morning transition from stable to unstable condition. •Continuous tracking of Mixed Layer Height (MLH) by ceilometer.•PM2.5 and NOx correlate inversely with MLH during daytime.•PM2.5 decreases by 14, 13 and 7 μgm−3 in December, January and February respectively for every 100 m increase in MLH.•Effect of dilution and accumulation by MLH on PM illustrated.